2014
DOI: 10.15868/socialsector.18140
|View full text |Cite
|
Sign up to set email alerts
|

Ready or Not? How Community Health Centers View Their Preparedness to Care for Newly Insured Patients

Abstract: By expanding access to affordable insurance coverage for millions of Americans, the Affordable Care Act will likely increase demand for the services provided by federally qualified health centers (FQHCs), an important source of care in low-income communities. A Commonwealth Fund survey asked health center leaders in 2013 about current and anticipated workforce challenges, as well as efforts under way to prepare for the increase in patients. The majority of FQHCs reported shortages of primary care doctors (56%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Prior research has shown that FQHCs deliver care of comparable or perhaps higher quality than other primary care practices, [15][16][17] but face challenges in areas such as recruiting staff or implementing health information technology. 18,19 Of course, federally qualified health centers likely represent a fraction of practices caring for disadvantaged patients, and little research has examined the primary care safety net more broadly.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has shown that FQHCs deliver care of comparable or perhaps higher quality than other primary care practices, [15][16][17] but face challenges in areas such as recruiting staff or implementing health information technology. 18,19 Of course, federally qualified health centers likely represent a fraction of practices caring for disadvantaged patients, and little research has examined the primary care safety net more broadly.…”
Section: Introductionmentioning
confidence: 99%
“…Providers working in FQHCs may face challenges related to increased patient load, and therefore FQHCs may experience higher staff turnover. Incentives to improve recruitment and retention of clinicians in underserved areas are being employed ( Abrams et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%